2001
DOI: 10.1016/s1097-2765(01)00393-8
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Human Arp2/3 Complex Reveals Critical Roles of Individual Subunits in Complex Structure and Activity

Abstract: The Arp2/3 complex is a seven-protein assembly that is critical for actin nucleation and branching in cells. Here we report the reconstitution of active human Arp2/3 complex after expression of all seven subunits in insect cells. Expression of partial complexes revealed that a heterodimer of the p34 and p20 subunits constitutes a critical structural core of the complex, whereas the remaining subunits are peripherally located. Arp3 is crucial for nucleation, consistent with it being a structural component of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
165
0
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(188 citation statements)
references
References 41 publications
18
165
0
5
Order By: Relevance
“…A function in VCA binding and in tethering Arp2 to the complex could both explain a loss of actin nucleation in ⌬arc40 extract. Our result is also largely consistent with the results from reconstitution experiments using human Arp2/3 subunit expressed in insect cells (33). Partial complex was purified from a reconstitution mixture that lacked both ARPC1 and ARPC5.…”
Section: Arpc1/arc40 Functions In Budding Yeastsupporting
confidence: 89%
“…A function in VCA binding and in tethering Arp2 to the complex could both explain a loss of actin nucleation in ⌬arc40 extract. Our result is also largely consistent with the results from reconstitution experiments using human Arp2/3 subunit expressed in insect cells (33). Partial complex was purified from a reconstitution mixture that lacked both ARPC1 and ARPC5.…”
Section: Arpc1/arc40 Functions In Budding Yeastsupporting
confidence: 89%
“…Intensive studies had revealed that VCA's ability to bind monomer actin through its V subdomain is critical for actin nucleation (Miki and Takenawa, 1998). The CA subdomain confers to N-WASP its binding ability to the Arp2/3 complex as evidenced by physicochemical assays (Machesky and Insall, 1998;Marchand et al, 2001) and x-ray crystallography and cross-linking experiments (Gournier et al, 2001;Robinson et al, 2001;Zalevsky et al, 2001). Actin polymerization, nucleation, and branching are enhanced in the presence of VCA protein in vitro Machesky et al, 1999;Rohatgi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…More recent evidence suggests further that WASp binding may induce conformational rearrangements that propagate through all seven subunits of the Arp2/3 complex (5,6). The p35/ARPC2 and p19/ARPC4 subunits form the structural core of the complex and mediate binding to the side of the mother filament (3,(7)(8)(9)(10). Functions of the remaining three subunits have remained elusive.…”
mentioning
confidence: 99%
“…Two biochemical studies found that the Arp2/3 complex lacking p40/ARPC1 shows severely reduced actin nucleation activity in vitro (8,15). p40/ARPC1 also binds to the VCA (verprolin homology domain, connector, acidic) domain of S. cerevisiae WASp (Las17) (15,16) and directly contacts two other subunits in the complex, p19/ARPC4 and p15/ARPC5 (3).…”
mentioning
confidence: 99%